Using Simple Instructional Videos to Improve Procedural Text Listening Skills of Students with Intellectual Disabilities - Novinda Pradnyani; Ni Made Rai Wisudariani; Ade Asih Susiari Tantri (FKIP - Universitas Riau, 2026)
Students with intellectual disabilities often experience difficulties in sustaining attention, retaining verbal information, and following sequential instructions, which can constrain procedural text listening performance. This classroom action research investigated the use of simple instructional videos to improve procedural text listening skills among seventh grade Culinary Arts students at SLB Negeri 2 Buleleng. The study was conducted in two cycles involving ten participating students and a collaborating homeroom teacher. Data were collected through classroom observation, performance tests, and structured interviews. The effectiveness of the intervention was evaluated primarily through students' performance test results, which were strengthened by classroom observation data documenting teacher implementation and student learning activities, as well as interview findings from teachers and students. Results showed that the mean listening performance score increased from 70.00 in Cycle I to 80.00 in Cycle II, while classical mastery increased from 50% to 80%, exceeding the predetermined 75% success criterion. Students also demonstrated stronger attention, better understanding of procedural sequences, greater independence during practice, and positive responses to video supported learning. The findings indicate that simple, concrete, repeatable, and contextually relevant instructional videos can support functional listening development for students with intellectual disabilities when integrated with visual scaffolds, teacher guidance, and authentic vocational practice.